Localismo, sobrevalorização do presente e história dos faxinais (Séc. XVIII - XIX) (Revista de História Regional, 2022)
Reflections on the history of faxinais, proposing its division into periods, as an alternative to the overvaluation of the present, the perspective of structuralism and localism, detected in some academic productions on the faxinalense theme. The initial phase, extends from the time before the arrival of Europeans until the beginning of the 19th century. The phase of occupation and enclosure, from the beginning of the 19th to the end of the 20th. And the current phase of social and political organization, which begins at the end of the 20th and beginning of the 21st, until the present. Thus, the classic model of the common fenced breeding site, as an experience restricted to a region, is integrated in the history of occupation and use of this type of areas.